RAD01: Development of a NUMTEK RAD01 Low-Cost, Portable Digital Gamma Radiation Detector - Khurelbaatar, Luvsanbat; Dashdondog, Erdenebaatar; Tumenjargal, Turtogtokh; Tumendemberel, Begzsuren; Urnukhsaikhan, Enerelt; Orgilsaikhan, Gerelmaa (Scientific transaction of the National University of Mongolia. Physics, 2024)
Additive manufacturing and open-source affordable instruction provide equal opportunities. Therefore, it is possible to quickly, compactly, and cheaply make expensive, scarce, and large devices in the previous century. The Geiger-Muller tube is used for the primary sensing component proposed and incorporates digital signal processing to ensure accurate and reliable measurement of gamma radiation. The performance of the developed detector is evaluated through experimental testing and comparisons with commercially available radiation detection devices. The results demonstrate the detector’s ability to provide precise and consistent measurements while remaining cost-effective. Moreover, its portability and user-friendly interface make it suitable for various applications, including environmental monitoring, nuclear safety, personal radiation exposure assessment, and, most importantly, educational purposes. This low-cost portable digital gamma radiation detector contributes to the field of radiation detection by presenting an accessible solution that addresses the financial limitations associated with conventional gamma radiation detectors.